Potential biogeographic distribution of the genus Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes) in Mexican coasts - Najera-Medellin, Jesús Alejandro (2019)
Seahorses (genus Hippocampus) are a group of threatened fish. Distribution maps present information for the conservation of biodiversity, correct management and protection of natural resources, and development of management plans.  In addition, they are the basis for further studies in taxonomy, biogeography, ecology, and evolution. With the purpose of assessing the efficiency and performance of different methods for the modeling potential distribution of the four species of the genus Hippocampus in Mexico, georeferenced occurrence points were collected from 1970 to 2017, and four predictive models were used to determine their potential distribution. Each model was assessed with a ROC curve analysis and a Cohen’s Kappa statistic. A Jacknife analysis was also conducted in the MaxEnt program to know the environmental variables that were more important in the model prediction. Results show that H. erectus and H. zosterae had a wide distribution in the coasts of the Gulf of Mexico; H. ingens shows a marked distribution along the coastal states of the Pacific Ocean while H. reidi has a more restricted distribution prediction in the Mexican Caribbean area. Bathymetry, distance to the coast, and chlorophyll concentration are the most determining factors in the probability of occurrence of the four species